2005
DOI: 10.1164/rccm.200412-1726oc
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Crossover Analysis of Out-of-Hospital Coronary Deaths and Air Pollution in Rome, Italy

Abstract: Air pollutants originating from combustion processes, including ultrafine particles, are related to fatal, nonhospitalized coronary events. The effect is stronger among people over 65 years of age, but is not limited to a group with a specific comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
105
3
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 59 publications
11
105
3
2
Order By: Relevance
“…Medication use in asthmatics also increased in association with the cumulative exposure to UFP over 5 or even 14 days (von Klot et al, 2002). Ru¨ckerl et al (2006) observe the highest increases in some blood markers in patients with coronary heart disease at a lag of 48 to 71 h. However, other studies observed immediate associations of UFP on mortality or morbidity, respectively (Forastiere et al, 2005;von Klot et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Medication use in asthmatics also increased in association with the cumulative exposure to UFP over 5 or even 14 days (von Klot et al, 2002). Ru¨ckerl et al (2006) observe the highest increases in some blood markers in patients with coronary heart disease at a lag of 48 to 71 h. However, other studies observed immediate associations of UFP on mortality or morbidity, respectively (Forastiere et al, 2005;von Klot et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Evidence suggests that increased PM concentrations mainly affect the cardiovascular and respiratory systems (Peters et al, 1997a(Peters et al, , 1999Gold et al, 2000;Ibald-Mulli et al, 2001;Brook et al, 2002;Devlin et al, 2003;Schulz et al, 2005) and are especially associated with increased cardiovascular hospital admissions (Schwartz, 1999;Zanobetti et al, 2000;Le Tertre et al, 2002;D'Ippoliti et al, 2003;von Klot et al, 2005;Dominici et al, 2006) or increased cardiovascular mortality (Clancy et al, 2002;Forastiere et al, 2005;Zeka et al, 2005;Ostro et al, 2006). The physical or chemical particle properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some limitations to our study, however, that may originate from unidirectional case-crossover studies. Such designs might be sensitive to trends in the exposure and the outcome [27,28]. There is the possibility of downward bias in this study due to the relatively short interval (1 week) between the hazard and control periods that may lead to low variability of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Confounding may occur because of time-varying risk factors [27,28], such as time of day or weather conditions, which were considered in the multivariate analysis. As individuals comprise study units in this type of study, this approach can assess effect modification by within-person factors; however, the statistical power of the method is lower than in time-series analysis [29,30].…”
Section: Discussionmentioning
confidence: 99%